Mi Voz, Mi Vida : Latino College Students Tell Their Life Stories - Gomez, Christina; Kilkenny, Robert; Garrod, Andrew, 1937- (Book collections on Project MUSE., 2007)
Amid the flurry of debates about immigration, poverty, and education in the United States, the stories in Mi Voz, Mi Vida allow us to reflect on how young people who might be most affected by the results of these debates actually navigate through American society. The fifteen Latino college students who tell their stories in this book come from a variety of socioeconomic, regional, and family backgrounds-they are young men and women of Mexican, Puerto Rican, Cuban, Dominican, Central American, and South American descent. Their insights are both balanced and frank, blending personal, anecdotal, political, and cultural viewpoints. Their engaging stories detail the students' personal struggles with issues such as identity and biculturalism, family dynamics, religion, poverty, stereotypes, and the value of education. Throughout, they provide insights into issues of racial identity in contemporary America among a minority population that is very much in the news. This book gives educators, students, and their families a clear view of the experience of Latino students adapting to a challenging educational environment and a cultural context-Dartmouth College-often very different from their childhood ones.